The Effect of Calcium Carbonate (CaCO3) and Polystyrene (PS) Composition on Contact Angle and Compressive Strength of Hydrophobic Cement Mortar. Issue 1 (1st July 2022) - Septiana, Delvi; Ratnawulan,; Syaputri, Oktaviani; Salam, Muhammad
Abstract: In the building there are several elements such as pillars, floors and walls. The wall is the outermost part of the building that directly receives changes in weather such as rain. As a result, the walls of the building are easily fragile and make the walls damaged. To reduce damage, it is necessary to test cement that is resistant to water (hydrophobic) so that the walls of the building are not easily damaged by water and durable with the help of hydrophobic agent additives in the form of CaCO3 and polystyrene. The purpose of this study was to investigate the effect of variations in the composition of CaCO3 /polystyrene on the contact angle of the hydrophobic layer and the compressive strength of portland cement. Precursors were made by varying the composition of CaCO3 1%, 2%, 3% and polystyrene/tetrahydrofuran 1:0, 065; 2:0, 065; 3;0, 065 and the calcination temperature used was 60°C using an oven. The optimum contact angle measurement results were obtained at the composition variation of CaCO3 3% and Polystyrene 3:0.065, which was 114.986° and the highest compressive strength value was at variations in the composition of CaCO3 1% and Polystyrene 3:0, 065, which was 238.10 kg/cm 2 .